Postures d’auteurs et représentation de la langue : - Sara De Balsi (Contextes, 2025)
This article examines the two categories of class defector and translingual writer, on the assumption that they can shed light on each other. While the writers themselves recognize a familiarity between the experience of language and class change, we analyze this proximity from the point of view of access to the literary field, discourse and narrative. An example of the intersection between the two categories, writers who arrived in the French language during childhood, is examined in the conclusion.